ANALISIS CITRA PEREMPUAN DALAM NOVEL HEARTBREAK MOTEL KARYA IKA NATASSA - Ayu Lestari; Sri Suryana Dinar; Fahruddin Hanafi (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study aims to describe the image of women in the novel Heartbreak Motel by Ika Natassa. The method used in this study is qualitative descriptive method. The data source in this study is the novel Heartbreak Motel by Ika Natassa published by GM Pustaka Utama Publishing Agency on April 8, 2022, consisting of 400 pages. This study focuses on the image of women put forward by Sugihastuti in the novel Heartbreak Motel. The data collection techniques. Based on the results of the study, the image of women in the novel Heartbreak Motel is a woman’s self-image and also a woman’s social image. Physically, Ava is depicted as a very fragile, attractive woman, long-haired, beautiful and has an ideal body. Psychologically, Ava is depicted as an emotional, sensitive person, tends to be interverted and keeps her feelings to herself. In her family, Ava is depicted as a child who lovers her mother, being an obedient woman despite being treated badly by her boyfreind. Society’s view of her is sometimes negative when she chooses to break up with her actor boyfriend so that she is considered a social climber by netizens. Based on this, it can be concluded that the social image pf women significantly influences the main character’s self-image. It’s clear that every trauma Ava experienced in her past has mae her a more withdrawn person, preferring to keep her feelings to herself.